Imaging and Quantification of Myelin Integrity After Injury With Spectral Confocal Reflectance Microscopy - Gonsalvez, David G.; Yoo, SangWon; Fletcher, Jessica L.; Wood, Rhiannon J.; Craig, Georgina A.; Murray, Simon S.; Xiao, Junhua (Frontiers in Molecular Neuroscience, 2019)
Developing a high throughput approach to quantify the extent of myelin integrity in pre-clinical models of demyelinating diseases will enhance our capacity to identify novel therapies for myelin repair. In light of the technical limitations of Electron Microscopy and immunohistochemical analyses of myelination, we have utilized a novel imaging technique, Spectral Confocal Reflectance (SCoRe) microscopy. SCoRe takes advantage of the optically reflective properties of compact myelin allowing the integrity of compact myelin to be quantified over the course of the cuprizone-induced model of central demyelination. We applied SCoRe imaging on fixed frozen brain sections. SCoRe analysis of control mice identified an increase in corpus callosum myelination during the period of cuprizone administration and recovery, suggesting that the normal developmental processes of myelination are ongoing at this time. Importantly, analysis of mice subjected to cuprizone identified a significant reduction in compact myelin in both rostral and caudal corpus callosum compared to age-matched control mice. SCoRe microscopy also allowed the visualisation and quantification of the amount of myelin debris in demyelinating lesions. Combining SCoRe imaging with immunohistochemistry, we quantified the amount of myelin debris within IBa1+ microglia and found that 11% of myelin debris colocalized in microglia irrespective of the callosal regions, with the vast majority of debris outside of microglia. In summary, we have demonstrated that SCoRe microscopy is an effective and powerful tool to perform both quantitative and qualitative analysis of compact myelin integrity in health or after in injury in vivo, demonstrating its future application in high throughput assessment and screening of the therapeutic efficacy of myelin repair therapies in pre-clinical animal models of demyelinating diseases.